2023
DOI: 10.3389/fphys.2023.1152301
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the unique characteristics of the mandible to improve clinical approaches to mandibular regeneration

Abstract: The mandible (lower jaw) bone is aesthetically responsible for shaping the lower face, physiologically in charge of the masticatory movements, and phonetically accountable for the articulation of different phonemes. Thus, pathologies that result in great damage to the mandible severely impact the lives of patients. Mandibular reconstruction techniques are mainly based on the use of flaps, most notably free vascularized fibula flaps. However, the mandible is a craniofacial bone with unique characteristics. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Furthermore, it is of clinical interest to apply the proposed approach for exploring complex image properties of human mandibles for improving the diagnostics and treatment of facial trauma. It has recently been reported that by considering the uniqueness of the mandible can enhance clinical approaches to mandibular regeneration in order to avoid postsurgical complications [ 1 ]. In parallel to precision medicine [ 31 ], precision dentistry [ 32 , 33 ] is an emerging area of research that has potential to achieve precise dental diagnostics and targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is of clinical interest to apply the proposed approach for exploring complex image properties of human mandibles for improving the diagnostics and treatment of facial trauma. It has recently been reported that by considering the uniqueness of the mandible can enhance clinical approaches to mandibular regeneration in order to avoid postsurgical complications [ 1 ]. In parallel to precision medicine [ 31 ], precision dentistry [ 32 , 33 ] is an emerging area of research that has potential to achieve precise dental diagnostics and targeted treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, understanding characteristics of the mandible such as its morphology, physiology and genetic profile can be helpful for improving mandibular reconstruction. As a result, it can accelerate the healing process and prevent the patient from postsurgical complications [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…-Mice have a different dental development and signaling pathways than humans: while all teeth are laid down prenatally in mice, in humans, the formation of the second and third molars only occurs postnatally via the replacement dentition, parallel to the formation of the first symptoms of classic cherubism. -While the mandible originates from the cranial neural crest, the bones of the limbs are of mesodermal origin [59]. Because tubular bone is formed mesenchymally, "neural crest cells (NCCs)" derive from dorsal side of the neural tube; they proliferate rapidly and migrate along predetermined, well-characterized routes into developing frontonasal plate and gill arches.…”
Section: Summarized Evaluation From a Semantic Animal Experiment And ...mentioning
confidence: 99%
“…Med. 2024, 13, x FOR PEER REVIEW 7 of 11 -While the mandible originates from the cranial neural crest, the bones of the limbs are of mesodermal origin [59]. Because tubular bone is formed mesenchymally, "neural crest cells (NCCs)" derive from dorsal side of the neural tube; they proliferate rapidly and migrate along predetermined, well-characterized routes into developing frontonasal plate and gill arches.…”
Section: Summarized Evaluation From a Semantic Animal Experiment And ...mentioning
confidence: 99%